(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The goal of the resistance of the local peoples of the Central Asian region to the Oirot Kalmaks was the desire to lead an independent caravan, trading freely in a free economy, not dependent on external enemies, and establishing peaceful diplomatic relations with neighboring peoples. Since the way of life of nomadic peoples was close to each other, they did not differ much from neigh- boring peoples. Everyone had their own life, culture close to each other. Especially in this regard, nomads living in the region of the Yenisei, Fergana, Tien Shan, as well as neighboring Kazakhs and Uzbeks of nearby areas, political relations with the Karakalpak people. They even fought against external enemies together.